1996
DOI: 10.7557/2.16.4.1238
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Caribou Habitat Management Strategy for Northwestern Ontario: Running the Gauntlet

Abstract: A management strategy for woodland caribou (Rangifer tarandus caribou) habitat is being developed in northwestern Ontario. This strategy is based upon a set of draft Timber Management Guidelines for the Provision of Woodland Caribou Habitat. These guidelines recommend maintaining a sustainable supply of winter habitat within large tracts of old forest, protecting calving areas and minimizing human disturbance. Due to the large temporal and spatial scale of caribou habitat management, an ecosystem-based approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 1 publication
2
23
0
Order By: Relevance
“…This study, like Harris (1996) and , found that reindeer lichens grow on substrates created by logging activities including stumps, slash, and haul roads. The persistence of undisturbed reindeer lichens and growth of reindeer lichen fragments, however, likely accounted for the higher cover of reindeer lichens on burned sites than on logged sites of the same age since disturbance.…”
Section: Fragment Growthsupporting
confidence: 55%
See 3 more Smart Citations
“…This study, like Harris (1996) and , found that reindeer lichens grow on substrates created by logging activities including stumps, slash, and haul roads. The persistence of undisturbed reindeer lichens and growth of reindeer lichen fragments, however, likely accounted for the higher cover of reindeer lichens on burned sites than on logged sites of the same age since disturbance.…”
Section: Fragment Growthsupporting
confidence: 55%
“…Fragments on logged sites presumably result from the mechanical break-up of existing reindeer lichens by timber harvesting and site preparation activities (Harris, 1996). This study and Harris (1996) found that reindeer lichens which were undisturbed by timber harvest and site preparation persisted and were still evident on the oldest logged sites.…”
Section: Fragment Growthmentioning
confidence: 71%
See 2 more Smart Citations
“…Racey & Armstrong (1996) summarized some of the early consultation efforts that were focused on the development of a caribou habitat management approach for northwestern Ontario. A stakeholder advisory panel provided key advice as part of this process (Greig & Duinker, 1996).…”
Section: Public Consultation and Engagementmentioning
confidence: 99%